The prisoner in the castle [compact disc, unabridged] : a Maggie Hope mystery - MacNeal, Susan Elia (MacNeal, Susan Elia. Maggie Hope mystery, 2018)
While being held prisoner on a remote Scottish island, Maggie Hope, a spy and codebreaker, must find the person responsible for killing the other spies before she becomes the next victim.